Fen1 mutations that specifically disrupt its interaction with PCNA cause aneuploidy-associated cancer - Zheng, Li (Nature Publishing Group, 2011)
DNA replication and repair are critical processes for all living organisms to ensure faithful duplication and transmission of genetic information. Flap endonuclease 1 (Fen1), a structure-specific nuclease, plays an important role in multiple DNA metabolic pathways and maintenance of genome stability. Human FEN1 mutations that impair its exonuclease activity have been linked to cancer development. FEN1 interacts with multiple proteins, including proliferation cell nuclear antigen (PCNA), to form various functional complexes. Interactions with these proteins are considered to be the key molecular mechanisms mediating FEN1's key biological functions. The current challenge is to experimentally demonstrate the biological consequence of a specific interaction without compromising other functions of a desired protein. To address this issue, we established a mutant mouse model harboring a FEN1 point mutation (F343A/F344A, FFAA), which specifically abolishes the FEN1/PCNA interaction. We show that the FFAA mutation causes defects in RNA primer removal and long-patch base excision repair, even in the heterozygous state, resulting in numerous DNA breaks. These breaks activate the G2/M checkpoint protein, Chk1, and induce near-tetraploid aneuploidy, commonly observed in human cancer, consequently elevating the transformation frequency. Consistent with this, inhibition of aneuploidy formation by a Chk1 inhibitor significantly suppressed the cellular transformation. WT/FFAA FEN1 mutant mice develop aneuploidy-associated cancer at a high frequency. Thus, this study establishes an exemplary case for investigating the biological significance of protein-protein interactions by knock-in of a point mutation rather than knock-out of a whole gene.